Innovation, Intellectual Property, and Economic Growth. - Greenhalgh, C; Rogers, M (Princeton University Press, 2010)
What drives innovation? How does it contribute to the growth of firms, industries, and economies? And do intellectual property rights help or hurt innovation and growth? Combining microeconomics, macroeconomics, and theory with empirical analysis drawn from the United States and Europe, this book describes the complex process of innovation. In four sections, the book addresses the nature of innovation and intellectual property, the microeconomics and macroeconomics of innovation, and economic policy at the firm and macroeconomic levels. Among the topics explored are the role of intellectual property in creating incentives to innovate; the social returns of innovation; the creation and destruction of jobs by innovation; whether more or fewer intellectual property rights would give firms better incentives to innovate; and the contentious issues surrounding international treaties on intellectual property.